2021
DOI: 10.1155/2021/6649640
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Laparoscopy in Comprehensive Staging Operation of Ovarian Cancer Based on Electronic Medical Blockchain Technology

Abstract: Ovarian cancer has always entangled most women. Studies have shown that the prevalence of ovarian cancer ranks third in female reproductive malignancies, and the mortality rate has always been the highest. The reason is mainly because the diagnosis and treatment of preovarian cancer has always been a big problem. However, the emergence of laparoscopy can well solve this problem, especially laparoscopy assisted by blockchain technology, which plays a huge role in the overall staging of ovarian cancer. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%